2022
DOI: 10.3390/su142416987
|View full text |Cite
|
Sign up to set email alerts
|

How Does Digital Economy Affect Rural Revitalization? The Mediating Effect of Industrial Upgrading

Abstract: Since the reform and opening up in 1978, China’s economy has grown significantly, but rural development still lags. China has implemented a rural revitalization strategy to reduce the gap between urban and rural areas. Meanwhile, the digital economy has gradually become a new economic growth engine for China. With the digitalization of rural industries, the digital economy gradually integrated into rural development and revitalization. However, how the digital economy impacts rural revitalization remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Green entrepreneurship plays a crucial role in facilitating the transition to sustainable solutions [46]. The results are corroborated by the research conducted by Cen et al [70], which investigated the influence of Industry 4.0 technologies on the capacity of industrial upgrading to enhance rural revitalization.…”
Section: Discussion Of Findings and Their Implicationsmentioning
confidence: 57%
“…Green entrepreneurship plays a crucial role in facilitating the transition to sustainable solutions [46]. The results are corroborated by the research conducted by Cen et al [70], which investigated the influence of Industry 4.0 technologies on the capacity of industrial upgrading to enhance rural revitalization.…”
Section: Discussion Of Findings and Their Implicationsmentioning
confidence: 57%
“…According to the theory of development economics, economic resilience is an important source for the government when seeking to maintain its competitive advantage in dealing with risks. Therefore, economic resilience is a process by which to test whether the government can maintain, recover, adapt or transform the economy through effective governance under the impact of risks [16], which is an effective measure of the goal and value orientation of governance.…”
Section: Theoretical Basis and Research Hypothesis 21 The Goal Orient...mentioning
confidence: 99%
“…The first direction is research on the coupling and coordination relationship between rural revitalisation and digital economy. For example, Tao Cen et al, based on their research on the coupling of the development of the digital economy and rural revitalisation in 11 cities in Zhejiang Province, prove that the digital economy does indeed promote rural revitalisation and that performing industrial upgrades plays an important mediating role [1]. Meng Lingguo and Chen Wei (2022) conducted a study based on the coupling and coordinated development of rural finance and rural revitalisation in the Guangdong Province from 2016 to 2020; the results found that financial development has a significant positive spatial spillover effect on rural revitalisation.…”
Section: Literature Reviewmentioning
confidence: 99%